BUREAUCRATIC REFORM IN POVERTY ALLEVIATION - Puspitasari, Febriana Maya; Santoso, Edy (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This paper will review the bureaucratic reform movement in alleviating poverty which is very closely related to development goals, where development goals are basically to improve people's welfare. The ability to plan, organize and evaluate the implementation of development will affect the level of community welfare that will be achieved and this cannot be separated from the function of the government. Development also means making changes in social life with the emergence of innovation and hopes for improved development for the community. The concept of social welfare and social change is one of the fundamental issues in development. In the current era of communication there are many opportunities to improve the quality of life in order to get out of poverty. The Ministry of State Apparatus Empowerment and Bureaucratic Reform is currently focusing on development performance, and for starters the focus of its implementation is on poverty alleviation. Assistant Deputy for Policy Formulation and Coordination of the Implementation of Bureaucratic Reform of the Ministry of PANRB, namely Agus Uji Hantara as a guest speaker at the Focus Group Discussion (FGD) at the Regional Development Planning Agency Office of East Java Province on Thursday April 14 2022 said that the theme of poverty alleviation was taken because of the Covid pandemic -19 had a major impact on increasing the poverty rate. Therefore it is necessary to improve the quality of government governance through the implementation of bureaucratic reforms in reducing poverty. This was successfully implemented in West Java Province where based on data from the Central Statistics Agency (BPS) for 2021, the percentage of poverty in West Java Province fell to 7.97 percent from 8.43 percent the previous year. So that poverty alleviation policies are closely related to the success of bureaucratic reform which has an impact on poverty alleviation policies. Because the innovation-based people's economic recovery and growth, strengthening of the food security system, as well as the social protection system have so far been driven by government institutions.